SYNCHRONIZATION IN ENSEMBLE OF NONLINEARLY GLOBAL COUPLING RADIO ENGINEERING GENERATORS - Zhanabaev, Z.Zh.; Temirbayev, A.A.; Tarasov, S.B.; Rosenblum, M.; Almasbekov, N.E. (Recent Contributions to Physics, 2017)
The effect of synchronization has been studied in an ensemble of 20-global nonlinear coupling radio engineering oscillating elements. We illustrate the examples, which demonstrate complex quasiperiodic dynamics and dependence of order parameter on different synchronous regimes.